Pseudomonas syringae Differentiates into Phenotypically Distinct Subpopulations During Colonization of a Plant Host. (9th September 2016) - Rufián, José S.; Sánchez‐Romero, María‐Antonia; López‐Márquez, Diego; Macho, Alberto P.; Mansfield, John W.; Arnold, Dawn L.; Ruiz‐Albert, Javier; Casadesús, Josep; Beuzón, Carmen R.
Summary: Bacterial microcolonies with heterogeneous sizes are formed during colonization of Phaseolus vulgaris by Pseudomonas syringae . Heterogeneous expression of structural and regulatory components of the P. syringae type III secretion system (T3SS), essential for colonization of the host apoplast and disease development, is likewise detected within the plant apoplast. T3SS expression is bistable in the homogeneous environment of nutrient‐limited T3SS‐inducing medium, suggesting that subpopulation formation is not a response to different environmental cues. T3SS bistability is reversible, indicating a non‐genetic origin, and the T3SS HIGH and T3SS LOW subpopulations show differences in virulence. T3SS bistability requires the transcriptional activator HrpL, the double negative regulatory loop established by HrpV and HrpG, and may be enhanced through a positive feedback loop involving HrpA, the main component of the T3SS pilus. To our knowledge, this is the first example of phenotypic heterogeneity in the expression of virulence determinants during colonization of a non‐mammalian host.